A Study On The Use Of Shipping Container Booth As A Substitution Of Street Vendors Cart - Nurhayatu Nufut Alimin; Fidyani Samantha; Mulyadi Mulyadi; Ahmad Faizin (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2021)
The present study focused on the development of a compact living concept that is applied in commercial facilities, especially shipping container-booth. This study aimed to investigate the organization of container booths in Solo area from interior design perspectives, including its visual aesthetics, visual brand identity, and space function and organization of the container booth. The result of the study may depict the advantages of container booths, compared to conventional street food carts. This study was expected to provide adequate data to establish a new revenue-generating unit. To this end, a qualitative descriptive method was applied to obtain in-depth data related to the exterior and interior aspects of the booth. This study showed that container booth holds some advantages related to visual aesthetic aspects since it could be easily added with aesthetic elements for promotion media.  Container booth also allows a division of area that supports the seller's activity.